ANALISIS PENGARUH COST EFFICIENCY RATIO TERHADAP NET PROFIT MARGIN PADA PT BANK MANDIRI TBK CABANG â€œXâ€ SURABAYA - Handayani, Santiana (Jurnal Akuntansi AKUNESA, 2014)
Mandiri bank is the biggest bank concerning to assets, loan, and deposit. ?X? district is one of district of Mandiri bank in Surabaya. Banks is an institution which its main activity is fund raising from society then revolves it with purpose to generate revenue from which. Therefore it is important for bank to maintain public trust because the business activity is relying to the public trust. This research aims to examine the influence of cost efficiency ratio (CER) toward net profit margin (NPM). The object of this research is PT Bank Mandiri Tbk ?X? Departement of Surabaya during 2010 up to 2012. The background of this research done is due to the PT Bank Mandiri Tbk ?X? Departement of Surabaya bank?s low rate in obtaining NPM.Based on the research result, it is found that CER correlates to the NPM. NPM will be low when CER be in very high value. In this situation, CER had positive influence toward NPM.Keywords: Effective, CER, NPM